99.8k views
5 votes

log_(2)(2x + 1) - 5 log_(4)( {x}^(2) ) + 4 log_(2)(x)

1 Answer

4 votes

Evaluate each expression individually and then combine like terms:

5 log₄(x²) = 5
(log (x^(2)) )/(log (4) ) = 5
(log (x^(2)) )/(log (2^(2)) ) = 5
(2 log (x) )/(2 log (2) ) = 5 log₂x = log₂x⁵

4 log₂(x) = log₂(x)⁴ = log₂(x⁴)

**********************************************

log₂(2x + 1) - 5 log₄(x²) + 4 log₂(x)

= log₂(2x + 1) - log₂x⁵ + log₂(x⁴)

= log₂[(2x + 1)*(x⁴) ÷ x⁵]

= log₂
((2x+1)x^(4) )/(x^(5))

= log₂
(2x+1 )/(x)


User SRG
by
6.5k points